Tactical and strategic level planning in float glass manufacturing with co-production, random yields and substitutable products - Taşkın, Zeki Caner. (Thesis (M.S)-Bogazici University.Institute for Graduate Studies in Science and Engineering, 2005., 2005)
In this study, tactical and strategic level planning problems in float glass manufacturingare investigated. Float glass manufacturing is a continuous process which has some unique properties such as uninterruptible production, random yields, partiallycontrollable co-production compositions, complex relationships in sequencing ofproducts and substitutable products. Furthermore changeover times and costs are veryhigh and production speed depends significantly on the product mix. These characteristics render measurement and management of production capacity a significant task.The motivation for this study is a real life problem faced at Trakya Cam, which is the Şişecam company at flat glass market. Trakya Cam has multiple, geographically separatedproduction facilities and transportation of glass is expensive. Therefore logistics costs are significant. In this work we consider color campaign planning, multi-siteaggregate planning and strategic planning problems. We develop a decision supportsystem based on several mixed integer linear programming models in which productionand transportation decisions are given simultaneously. The system has been fully implemented and deployed at Trakya Cam. Comparison of production plan generatedby our system with manual production plan indicates a significant increase in levelof detail that can be handled, an increase in applicability of the production plan inthe complex production environment, ability to manage production capacity effectivelyand a significant decrease in transportation costs without a decrease in the quality of service.
Keywords: Glass trade.; Glass.